Spatiotemporal Variability Of Small Mammal Population Abundance In The Ecosystems Of The Lower Amu Darya Delta - Tlegenov, Markhabay Tolegenovich (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2026)
This paper analyzes the biotopic distribution, as well as certain population and demographic parameters of the community of murid rodents under different levels of population density of background (dominant) species.